Degradation of Indigo Carmine in Alkaline Dye-Mediated Direct Carbohydrate Fuel Cell. Issue 4 (23rd April 2021) - Wotton, Alexander; Yeung, Tracey; Huang, Fiona; Conibeer, Gavin; Zhao, Chuan; Stride, John; Patterson, Robert
Abstract : Indigo-carmine-mediated direct alkaline fuel cells have demonstrated superior power outputs over their non-mediated counterparts. Currently, the mechanism of mediation and stability of mediators are poorly understood. Upon exposure to highly alkaline solutions, we observed that the redox action of indigo carmine diminished, and significant currents were produced, indicating substantial degradation of the dye. The decomposition of indigo carmine at high pH and a poor thermal stability suggest that alternative mediators with low toxicity may be required to enable the widespread application of this device type.